2022
DOI: 10.3390/ijgi11070386
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Spatial Urban Expansion and Morphologic Landscapes East of Cairo, Egypt Using Time Series Satellite Imagery

Abstract: This study aims to monitor the magnitudes, rates, and directions of spatial urban expansions east of Cairo and their interactions with the initial morphologic landscapes. The approach relies on using CORONA satellite images acquired in 1969 with fine spatial resolution and time series images of Landsat and ASTER from 1984 to 2020. The CORONA images enable retrieval of the initial morphologic components, whereas the Landsat and ASTER images enable the spatial urban expansions to be mapped. The magnitudes of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…As the mission of CORONA was to provide images, especially of the Soviet Union and China [51], these two countries were featured in most LULC studies in which CORONA data were used. Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As the mission of CORONA was to provide images, especially of the Soviet Union and China [51], these two countries were featured in most LULC studies in which CORONA data were used. Our results showed that except for present-day Russia and China, CORONA imagery was also commonly used in India and Nepal; the Middle East (Iraq, Iran and Syria); Northern and Western Africa (Egypt, Mali and Senegal); and Central and Eastern Europe (Poland and Romania) [26,28,30,[42][43][44][52][53][54][55][56][57][58]. Some of these countries (e.g., Poland and Romania) have good coverage of CORONA imagery due to the goals of the program and the importance of the countries during the Cold War era [59][60][61].…”
Section: Discussionmentioning
confidence: 66%
“…Another frequently studied category is built-up areas in urban and peri-urban settings. For example, Shalaby et al [55] studied the directions of urban expansion and confirmed that the high spatial resolution of declassified images was sufficient to accurately map initial morphologic features. Pan et al [70] monitored the urban expansion of Xining City in China and confirmed the capability of CORONA and its resolution to quantify urban expansion.…”
Section: Discussionmentioning
confidence: 99%